Evaluating the effects of climate change on tree species abundance and distribution in the Italian peninsula - Attorre, Fabio; Alfò, Marco; De Sanctis, Michele; Francesconi, Fabio; Valenti, Roberto; Vitale, Marcello; Bruno, Franco (Applied Vegetation Science, 2011)
Question: What is the effect of climate change on tree species abundance and distribution in the Italian peninsula? Location: Italian peninsula. Methods: Regression tree analysis, Random Forest, generalized additive model and geostatistical methods were compared to identify the best model for quantifying the effect of climate change on tree species distribution and abundance. Future potential species distribution, richness, local colonization, local extinction and species turnover were modelled according to two scenarios (A2 and B1) for 2050 and 2080. Results: Robust Random Forest proved to be the best statistical model to predict the potential distribution of tree species abundance. Climate change could lead to a shift in tree species distribution towards higher altitudes and a reduction of forest cover. Pinus sylvestris and Tilia cordata may be considered at risk of local extinction, while the other species could ﬁnd potential suitable areas at the cost of a rearrangement of forest community composition and increasing competition. Conclusions: Geographical and topographical regional characteristics can have a noticeable inﬂuence on the impact of predicted climate change on forest ecosystems within the Mediterranean basin. It would be highly beneﬁcial to create a standardized and harmonized European forest inventory in order to evaluate, at high resolution, the effect of climate change on forest ecosystems, identify regional differences and develop speciﬁc adaptive management strategies and plans.
Keywords: generalized additive model; geostatistical; geostatistical methods; italian peninsula; methods; random forest; regression tree analysis

Characterization of mineral content in Quercus ilex leaves by photon and neutron activation analysis - Bruno, Franco; Capannesi, Geraldo; Gratani, Loretta; Manes, Fausto (Giornale botanico italiano, 1980)
Abstract As part of a research on the holm oak stand and the Mediterranean « macchia » of Castelporziano, this study has provided the mineral characterization of Quercus ilex leaves by means of photon and neutron activation analysis. Although there is no evidence to indicate a selective distribution of the elements in the trees' crowns, some correlations are of considerable interest. Highly significant correlation coefficients are observed for the following pairs of elements: Fe-Sc, Fe-Cr, Fe-Th, Fe-Eu.
doi: 10.1080/11263508009427960
Keywords: Castelporziano (voyant); leaves and twigs; nuclear analysis; Quercus ilex; Trace Elements